A high-temperature-resistant anti-adhesion superhard transparent fluorine-free green silicone coating and a preparation method thereof

CN120795789BActive Publication Date: 2026-10-20GUANGZHOU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511109958.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2026-10-20
Estimated Expiration
2045-08-08

AI Technical Summary

Technical Problem

[0003]尽管新兴溶胶-凝胶陶瓷涂层(如硅基涂层)消除了含氟化学品风险,但其本征脆性和弱界面粘接力会导致热循环下的灾难性分层,并在500次餐具刮擦周期内出现磨损失效

Benefits of technology

[0021]本发明提供的耐高温防黏附超硬透明无氟绿色有机硅涂层不含氟且具有长期热稳定性,在高温下不会释放有害物质;还具有高透光率和超高硬度,同时维持了有机硅类涂层固有的防污性,既满足了食品安全标准,又具备极佳的烹饪耐久性,透明的防污涂层还使锅具基材(如不锈钢的金属光泽或珐琅彩绘)的装饰性设计得以完整呈现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795789B_ABST
    Figure CN120795789B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-temperature-resistant anti-adhesion superhard transparent fluorine-free green silicone coating and preparation method thereof, belong to the technical field of silicone coating.The high-temperature-resistant anti-adhesion superhard transparent fluorine-free green silicone coating is prepared by using methyltrimethoxysilane, silica sol, hydroxyl silicone oil, isopropyl alcohol and water as raw materials, the design strategy of nanoscale polysiloxane coating is manufactured by the controllable sol-gel hydrolysis process of silicone precursor, the coating composed of nanometer SiO2 particles generated in situ is prepared, the defect minimization and highly crosslinked Si-O-Si network structure are realized, the nanoscale inorganic structure has long-term thermal stability, and the visible light transmittance of the coating can reach 98% due to the suppression of light scattering by subwavelength particle size.The uniform and close arrangement of the very small nanoparticles on the surface of the coating gives the coating superhigh hardness.In addition, the coating still maintains the inherent stain resistance of silicone coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organosilicon coating technology, and particularly relates to a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating and its preparation method. Background Technology

[0002] Silicone coatings have been widely used in various fields due to their antifouling properties, which repel a variety of contaminants. However, in some special high-temperature environments, such as non-stick cookware, silicone coatings cannot maintain good antifouling performance. Currently, the mainstream polytetrafluoroethylene (PTFE) system undergoes dangerous decomposition above 260°C, a temperature often exceeded during essential cooking techniques such as stir-frying or grilling, releasing carcinogenic perfluorooctanoic acid (PFOA) and endocrine-disrupting microplastics.

[0003] While emerging sol-gel ceramic coatings (such as silicone-based coatings) eliminate the risks associated with fluorinated chemicals, their inherent brittleness and weak interfacial adhesion lead to catastrophic delamination under thermal cycling and wear failure within 500 scraping cycles of tableware. This fragility stems from fundamental limitations in the material's design: achieving mechanical strength (>6H hardness) through high cross-linking density inevitably introduces light scattering defects, reducing optical transparency to below 85% and producing an undesirable frosted glass-like effect that impacts both durability and the visual clarity of decorative patterns. To make matters worse, the continued addition of perfluorinated compounds (PFCs) to commercial coatings directly violates increasingly stringent global regulations, such as the EU's comprehensive ban on PFAS (per- and polyfluoroalkyl substances) by 2023.

[0004] Therefore, there is an urgent need for an organosilicon coating that has good long-term thermal stability, high visible light transmittance, high hardness, and excellent anti-fouling properties to solve the above-mentioned technical problems. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green silicone coating and its preparation method. This invention provides a design strategy for a sustainable and high-performance alternative to polytetrafluoroethylene (PTFE) coatings, meeting food safety standards while possessing excellent cooking durability. Simultaneously, the transparent, stain-resistant coating allows the decorative design of cookware substrates (such as the metallic luster of stainless steel or enamel painting) to be fully displayed.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] This invention provides a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating, comprising the following raw materials in parts by weight: 40-80 parts of methyltrimethoxysilane, 50-80 parts of silica sol, 5-15 parts of hydroxyl silicone oil, 10-15 parts of isopropanol, and 5-25 parts of water.

[0008] Technical Principle: This invention uses methyltrimethoxysilane, silica sol, hydroxyl silicone oil, isopropanol, and water as raw materials to prepare a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating. Through a design strategy of controlling the sol-gel hydrolysis process of organosilicon precursors to manufacture nanoscale polysiloxane coatings, a coating with a matrix entirely composed of in-situ generated nano-SiO2 particles (2-20nm) was prepared. This achieved a defect-minimized, highly cross-linked Si-O-Si network structure. This nanoscale inorganic structure exhibits long-term thermal stability, and due to the subwavelength particle size suppressing light scattering, the visible light transmittance of the coating can reach 98%. Furthermore, the extremely small nanoparticles are uniformly and densely arranged on the coating surface, giving the coating ultra-high hardness. In addition, the coating still maintains the inherent anti-fouling properties of organosilicon coatings.

[0009] Further, it includes the following raw materials in parts by weight: 40-60 parts of methyltrimethoxysilane, 50-60 parts of silica sol, 5-10 parts of hydroxyl silicone oil, 10-13 parts of isopropanol and 5-15 parts of water.

[0010] Furthermore, the silica sol has a SiO2 content of 40% and a particle size of 5-20 nm.

[0011] Furthermore, the hydroxyl content of the hydroxyl silicone oil is 40%.

[0012] Furthermore, the water is deionized water.

[0013] Furthermore, the matrix of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating is composed of SiO2 particles with a particle size of 2-20 nm.

[0014] This invention provides a method for preparing a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating as described above, comprising the following steps:

[0015] Methyltrimethoxysilane, isopropanol, and water are mixed and stirred. Silica sol and hydroxyl silicone oil are then added, and stirring continues to yield a coating mixture. The coating mixture is poured onto a substrate and then thermo-cured to obtain the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating.

[0016] Furthermore, the stirring speed is 50-200 r / min, the stirring temperature is room temperature, and the stirring time is 4-12 h;

[0017] The stirring is continued at room temperature for 15-72 hours.

[0018] Furthermore, the temperature for heat curing is 150-300℃, and the time for heat curing is 40min-2h.

[0019] The present invention also provides an application of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating as described above in special high-temperature environments.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] The high-temperature resistant, non-adhesive, ultra-hard, transparent, fluorine-free green silicone coating provided by this invention is fluorine-free and has long-term thermal stability, and will not release harmful substances at high temperatures; it also has high light transmittance and ultra-high hardness, while maintaining the inherent anti-fouling properties of silicone coatings. It meets food safety standards and has excellent cooking durability. The transparent anti-fouling coating also allows the decorative design of cookware substrates (such as the metallic luster of stainless steel or enamel painting) to be fully presented. Attached Figure Description

[0022] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0023] Figure 1 The X-ray photoelectron spectrum of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating in Example 1 is shown below.

[0024] Figure 2 This is a SEM image of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1;

[0025] Figure 3 Infrared spectra of mixture 1, mixture 2, and coating mixture in Example 1;

[0026] Figure 4 The friction coefficients of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 and the friction coefficients after high-temperature treatment are shown.

[0027] Figure 5 The transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 and the transmittance after high-temperature treatment;

[0028] Figure 6 The nanoindentation curves of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 and the nanoindentation curves after high-temperature treatment are shown.

[0029] Figure 7 The coefficient of friction of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2;

[0030] Figure 8 The light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2;

[0031] Figure 9 The nanoindentation curve of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating in Example 2;

[0032] Figure 10 The coefficient of friction of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3;

[0033] Figure 11 The light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3;

[0034] Figure 12 The nanoindentation curves are those of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] This invention provides a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating, comprising the following raw materials in parts by weight: 40-80 parts of methyltrimethoxysilane, 50-80 parts of silica sol, 5-15 parts of hydroxyl silicone oil, 10-15 parts of isopropanol, and 5-25 parts of water.

[0038] The high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating provided by this invention comprises 40-80 parts by weight of methyltrimethoxysilane, more preferably 40-60 parts. The use of methyltrimethoxysilane in this invention is crucial. On the one hand, it ensures the reaction generates ultra-hard particles, improving the coating's hardness; on the other hand, the interaction between methyltrimethoxysilane and water solves the coating's light transmittance problem, achieving a transparent coating effect.

[0039] Based on 40-80 parts by weight of methyltrimethoxysilane, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating of the present invention comprises 50-80 parts of silica sol, more preferably 50-60 parts. The silica sol in the present invention, in combination with other raw materials, can further improve the hardness of the coating, achieving ultra-high hardness.

[0040] In a preferred embodiment, the silica sol has a SiO2 content of 40% and a particle size of 5-20 nm.

[0041] Based on 40-80 parts by weight of methyltrimethoxysilane, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating of this invention includes 5-15 parts of hydroxyl silicone oil, more preferably 5-10 parts. The hydroxyl silicone oil in this invention interacts with methyltrimethoxysilane and water to give the coating the effect of preventing adhesion to various liquids and solids, solving the problem of cookware coatings sticking to pans and achieving a non-stick effect.

[0042] In a preferred embodiment, the hydroxyl content of the hydroxyl silicone oil is 40%.

[0043] Based on 40-80 parts by weight of methyltrimethoxysilane, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating of the present invention includes 10-15 parts of isopropanol, more preferably 10-13 parts. Isopropanol is used as a solvent in the present invention.

[0044] Based on 40-80 parts by weight of methyltrimethoxysilane, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating of the present invention includes 5-25 parts of water, more preferably 5-15 parts; the water is deionized water.

[0045] In a preferred embodiment, the matrix of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating is composed of SiO2 particles with a particle size of 2-20 nm.

[0046] This invention provides a method for preparing a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating as described above, comprising the following steps:

[0047] Methyltrimethoxysilane, isopropanol, and water are mixed and stirred. Silica sol and hydroxyl silicone oil are then added, and stirring continues to yield a coating mixture. The coating mixture is poured onto a substrate and then thermo-cured to obtain the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating.

[0048] In a preferred embodiment, before adding the silica sol and hydroxyl silicone oil, a step of pre-mixing the silica sol and hydroxyl silicone oil is included; by pre-mixing the silica sol and hydroxyl silicone oil together before adding them, the antifouling ability of the coating can be improved.

[0049] In a preferred embodiment, the stirring speed is 50-200 r / min, more preferably 80-150 r / min; the stirring temperature is room temperature; and the stirring time is 4-12 h, more preferably 6-10 h.

[0050] In a preferred embodiment, the temperature for continued stirring is room temperature, and the stirring time is 15-72 hours, more preferably 24-72 hours. This invention ensures the transparency of the coating by controlling the temperature and time of continued stirring.

[0051] In a preferred embodiment, the thickness of the casting is 20-40 μm.

[0052] In a preferred embodiment, the substrate is selected from a glass plate or a tin plate.

[0053] In a preferred embodiment, the temperature for heat curing is 150-300°C, and the time for heat curing is 40 min-2 h.

[0054] This invention also provides an application of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating as described above in special high-temperature environments. Special high-temperature environments include aerospace, high-temperature industrial reactors, or special protective equipment.

[0055] In this embodiment of the invention, room temperature refers to "25±2℃".

[0056] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels.

[0057] In the following embodiments, the performance testing method is as follows:

[0058] 1. Coefficient of friction: The MXD-02 friction coefficient meter of Jinan Saicheng Instruments was used with a load of 200g and a pulling speed of 100mm / min.

[0059] 2. Transmittance: The transmission spectrum of the coating was measured in the range of 400–800 nm using a UV-Vis spectrophotometer (Varian Cary 7000 spectrophotometer), with bare glass as a reference.

[0060] 3. Hardness: Nanoindentation testing was conducted at 25°C using a nanoindentation machine (Bruker Hysitron TI980) equipped with Berkovich diamond tips. The maximum load was 1000 μN, and the loading and unloading rates were both 100 μN / s for each force loading, holding, and unloading cycle. The nanoindentation hardness and effective Young's modulus were calculated using the Oliver Pharr method.

[0061] 4. Water contact angle: The contact angle (CAs) was measured using a contact angle measuring instrument (JC2000A) with a droplet (water) volume of 5 μL.

[0062] 5. Anti-sticking effect: Based on the carbon absorptivity (ca) of water and n-hexadecane on the surface of the glass plate coated with a fluorine-free green silicone coating and the surface of the uncoated glass plate, the surface energy of the coated glass plate was calculated. The surface energy of the uncoated glass plate was 54.66 mJ / m². 2 .

[0063] 6. High temperature test: The coating is tested after being subjected to short-term (1h) extreme temperature treatment at 400℃ and 500℃.

[0064] Example 1

[0065] A high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating is composed of the following raw materials in parts by weight: 40 parts methyltrimethoxysilane, 50 parts silica sol, 5 parts hydroxyl silicone oil, 10 parts isopropanol, and 5 parts deionized water; wherein the silica sol has a SiO2 content of 40% and a particle size of 5-20 nm; and the hydroxyl content of the hydroxyl silicone oil is 40%.

[0066] The preparation method of the above-mentioned high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating is as follows: Methyltrimethoxysilane and isopropanol are mixed with water and stirred at 100 r / min for 7 h to obtain mixture 1; a mixture of hydroxyl silicone oil and silica sol (pre-mixed and stirred evenly, mixture 2) is added to the obtained mixture 1, and stirring is continued at room temperature for 1 day to obtain coating mixture; the obtained coating mixture is poured onto a glass plate with a pouring thickness of 20 μm, and heat-cured at 300℃ for 40 min to obtain a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating.

[0067] Figure 1 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating used in Example 1. From... Figure 1 It can be seen that the coating forms a stable silicon cross-linked network.

[0068] Figure 2 This is a SEM image of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating from Example 1. (From...) Figure 2 As can be seen, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 is smooth and uniform.

[0069] Figure 3 The infrared spectra of mixture 1, mixture 2, and the coating mixture in Example 1 are shown. Figure 3 In this context, prepolymer represents the coating mixture, particle 1 represents mixture 1, and particle 2 represents mixture 2. From... Figure 3 It can be seen that an organosilicon coating was successfully synthesized using methyltrimethoxysilane, silica sol, hydroxyl silicone oil, isopropanol and deionized water as raw materials.

[0070] Figure 4The coefficient of friction is shown for the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1, and the coefficient of friction after high-temperature treatment. From Figure 4 It can be seen that the coefficient of friction of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 is about 0.2. After being treated at high temperatures of 400℃ and 500℃, its coefficient of friction did not change significantly, indicating that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating provided by the present invention has excellent high-temperature resistance, and further proves the stability of the smoothness of the coating surface.

[0071] Figure 5 The transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 is shown, as well as the transmittance after high-temperature treatment. From... Figure 5 As can be seen, the light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1 is about 98%. At 400°C, the visible light transmittance of the coating remains above 92%, and although it decreases at 500°C, it still maintains a light transmittance of over 87%, which does not affect the display of the pattern under the coating. This indicates that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating provided by the present invention has high light transmittance and excellent high-temperature resistance.

[0072] Figure 6 The images show the nanoindentation curves of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 1, and the nanoindentation curves after high-temperature treatment. According to... Figure 6 The curves in the figure show that the nanoindentation hardness and effective Young's modulus of the coating were calculated using the Oliver Pharr method. The results show that the hardness of the coating is 13.32 GPa at room temperature, 12.82 GPa at 400℃, and 25.47 GPa at 500℃; the modulus of the coating is 1.62 GPa at room temperature, 1.75 GPa at 400℃, and 3.21 GPa at 500℃. It can be seen that high temperature treatment not only does not cause adverse changes in the hardness and modulus of the coating, but also significantly improves the hardness of the coating. This indicates that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating provided by this invention has high-temperature resistance and long-lasting mechanical resilience.

[0073] Example 2

[0074] A high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating is composed of the following raw materials in parts by weight: 80 parts methyltrimethoxysilane, 80 parts silica sol, 15 parts hydroxyl silicone oil, 15 parts isopropanol, and 25 parts deionized water; wherein the silica sol has a SiO2 content of 40% and a particle size of 5-20 nm; and the hydroxyl content of the hydroxyl silicone oil is 40%.

[0075] The preparation method of the above-mentioned high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating is as follows: Methyltrimethoxysilane and isopropanol are mixed with water and stirred at 100 r / min for 10 h to obtain mixture 1; a mixture of hydroxyl silicone oil and silica sol (pre-mixed and stirred evenly, mixture 2) is added to the obtained mixture 1, and stirring is continued at room temperature for 1 day to obtain coating mixture; the obtained coating mixture is poured onto a glass plate with a pouring thickness of 40 μm, and heat-cured at 180℃ for 40 min to obtain a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating.

[0076] Figure 7 The coefficient of friction is the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating used in Example 2. From... Figure 7 As can be seen, the coefficient of friction of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2 is about 0.2, indicating that the coating has excellent friction resistance.

[0077] Figure 8 This refers to the light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2. From... Figure 8 As can be seen, the light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2 is about 98%, indicating that the coating has excellent light transmittance and can achieve a transparent effect.

[0078] Figure 9 The image shows the nanoindentation curve of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2. From... Figure 9 It can be seen that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 2 has durable mechanical resilience. According to... Figure 9 The curves in the figure were used to calculate the nanoindentation hardness and effective Young's modulus of the coating using the Oliver Pharr method. The results showed that the hardness of the coating at room temperature was 11.84 GPa and the modulus of the coating was 1.68 GPa.

[0079] Example 3

[0080] A high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating is composed of the following raw materials in parts by weight: 60 parts methyltrimethoxysilane, 60 parts silica sol, 10 parts hydroxyl silicone oil, 13 parts isopropanol, and 15 parts deionized water; wherein the silica sol has a SiO2 content of 40% and a particle size of 5-20 nm; and the hydroxyl content of the hydroxyl silicone oil is 40%.

[0081] The preparation method of the above-mentioned high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating is as follows: Methyltrimethoxysilane and isopropanol are mixed with water and stirred at 100 r / min for 6 h to obtain mixture 1; a mixture of hydroxyl silicone oil and silica sol (pre-mixed and stirred evenly, mixture 2) is added to the obtained mixture 1, and stirring is continued at room temperature for 1 day to obtain coating mixture; the obtained coating mixture is poured onto a glass plate with a pouring thickness of 30 μm, and heat-cured at 150℃ for 2 h to obtain a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating.

[0082] Figure 10 The coefficient of friction is the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating used in Example 3. From... Figure 10 It can be seen that the coefficient of friction of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3 is 0.25.

[0083] Figure 11 The transmittance is the light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3. From... Figure 11 As can be seen, the light transmittance of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3 is about 98%, indicating that the coating has excellent light transmittance and can achieve a transparent effect.

[0084] Figure 12 The image shows the nanoindentation curve of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3. From... Figure 12 It can be seen that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating in Example 3 has durable mechanical resilience. According to... Figure 12 The curves in the figure were used to calculate the nanoindentation hardness and effective Young's modulus of the coating using the Oliver Pharr method. The results showed that the hardness of the coating at room temperature was 15.71 GPa and the modulus of the coating was 1.64 GPa.

[0085] The coefficient of friction, light transmittance, water contact angle and surface energy of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coatings prepared in Examples 1-3 are shown in Table 1.

[0086] Table 1

[0087]

[0088] As shown in Table 1, the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating provided by this invention has a coefficient of friction of 0.2-0.25, a light transmittance of 98%, a water contact angle of 93.576-105.356°, and a surface energy of 22.39-25.26 mJ / m². 2 This indicates that the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green silicone coating provided by the present invention has the characteristics of abrasion resistance, high visible light transmittance, and excellent anti-fouling properties.

[0089] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating, characterized in that, The raw material consists of the following components in parts by weight: 40-60 parts methyltrimethoxysilane, 50-60 parts silica sol, 5-10 parts hydroxy silicone oil, 10-13 parts isopropanol and 5-15 parts water; The preparation method includes the following steps: mixing methyltrimethoxysilane, isopropanol and water, stirring, adding silica sol and hydroxyl silicone oil, and continuing to stir to obtain a coating mixture; pouring the coating mixture onto a substrate, and heat curing to obtain the high-temperature resistant, non-adhesive, ultra-hard, transparent, fluorine-free green organosilicon coating. The matrix of the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating is composed of SiO2 particles with a particle size of 2-20nm.

2. The method for preparing the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating according to claim 1, characterized in that, The silica sol has a SiO2 content of 40% and a particle size of 5-20 nm.

3. The method for preparing the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free, green organosilicon coating according to claim 1 or 2, characterized in that, The hydroxyl content of the hydroxyl silicone oil is 40%.

4. The method for preparing the high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating according to claim 1, characterized in that, The water is deionized water.

5. The preparation method according to claim 1, characterized in that, The stirring speed is 50-200 r / min, the stirring temperature is room temperature, and the stirring time is 4-12 h; The temperature for continued stirring is room temperature, and the stirring time is 15-72 hours.

6. The preparation method according to claim 1, characterized in that, The temperature for heat curing is 150-300℃, and the time for heat curing is 40 min-2 h.

7. The application of a high-temperature resistant, anti-adhesion, ultra-hard, transparent, fluorine-free green organosilicon coating prepared by the method according to any one of claims 1-6 in special high-temperature environments.

Citation Information

Patent Citations

  • Antimicrobial non-viscous aqueous inorganic nano coating priming paint and preparation method thereof

    CN104761935A

  • Antifouling super-smooth hydrophobic coating as well as preparation method and application thereof

    CN119060632A